2012
DOI: 10.1097/mao.0b013e31825f24ba
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Surgical Benefits and Problems of Chronic Otitis Media and Middle Ear Cholesteatoma in Elderly Patients Older Than 70 Years

Abstract: Tympanoplasty in elderly patients older than 70 years seems to be as safe as when performed in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is characterized by sclerotic and hyaline degeneration of the submucosal collagen layer of the middle ear [19] and can result in ossicular chain transection or fixation. In the present study, Wullstein type I was the most commonly performed tympanoplasty in patients of all ages with chronic perforated otitis media, which was consistent with previous reports [2,4,20] . We also found the proportions of Wullstein types III and IV tympanoplasty to be significantly higher in the elderly group than in the middle group, as suggested by a previous report that found that the proportion of patients undergoing Wullstein type III with columella increased with age [20] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is characterized by sclerotic and hyaline degeneration of the submucosal collagen layer of the middle ear [19] and can result in ossicular chain transection or fixation. In the present study, Wullstein type I was the most commonly performed tympanoplasty in patients of all ages with chronic perforated otitis media, which was consistent with previous reports [2,4,20] . We also found the proportions of Wullstein types III and IV tympanoplasty to be significantly higher in the elderly group than in the middle group, as suggested by a previous report that found that the proportion of patients undergoing Wullstein type III with columella increased with age [20] .…”
Section: Discussionsupporting
confidence: 81%
“…Many researchers have investigated the relationship between age and the results of tympanoplasty in chronic otitis media [1,2] . Tympanoplasty in elderly patients is acceptable nowadays, and some have noted that postoperative hearing results are significantly improved in elderly patients and that there are no disadvantages in results compared to younger patients [3,4] , although preoperative bone-conduction thresholds gradually worsen with age. It is, however, often recognized during the operation that tympanoplasty can be technically more difficult in elderly patients than in younger patients because of severe middle ear conditions, including mucosal inflammation, tympanosclerosis, and destruction of the ossicular chain.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of tympanosclerosis was reported to be 18.6% in patients aged > 70 years by Shinnabe et al [10]. This rate was found to be 5.5% [12] and 11.6% [13] in the adult group.…”
Section: Discussionmentioning
confidence: 89%
“…Some authors reported that age is a significant prognostic factor for the success of tympanoplasty and that almost all tympanoplasty operations over 50 years of age may result in functional failure [9]. Shinnabe et al showed that in elderly patients with chronic otitis media without cholesteatoma, compared to before and after surgery, there was a statistically significant improvement in ABG, and ear discharge disappeared in 98% of patients [10]. Shishegar et al demonstrated in their study; there was no significant relationship between age and the success rate of tympanoplasty [11].…”
Section: Discussionmentioning
confidence: 99%
“…This inclination may be brought about by the expanded surgical (and nonsurgical) options for hearing augmentation following cholesteatoma surgery, 20 and by the increasing reports in the literature of favorable hearing outcomes in elderly patients following tympanoplasty procedures. [21][22][23] In this Australian national hospital database study, there was evidence of an increased adoption of a less invasive approach to the management of cholesteatoma by reference to CWU procedures.…”
Section: Discussionmentioning
confidence: 94%